THROMBOCYTOPENIA IN PATIENTS WITH MYELODYSPLASTIC SYNDROMES - STILL AN UNSOLVED PROBLEM - May Basood; Howard S. Oster; Moshe Mittelman (Mediterranean Journal of Hematology and Infectious Diseases)
The myelodysplastic syndromes (MDS) are a group of clonal bone marrow (BM) stem cell disorders, characterized by ineffective hematopoiesis, peripheral cytopenias and hematologic cellular dysfunction, as well as potential transformation to acute leukemia.